Determination of Sorbic Acid in Cheese Samples by Rapid HPLC-DAD Method - Ayşe Özdemir; Senem Şanlı; Barış Sardoğan; Seyfi Sardoğan (International Journal of Analytical Chemistry)
The sorbic acid and its salts have been widely used in the food industries for many years as important food preservatives in order to inhibit the growth of various bacteria, yeasts, and fungi in acidic media. The health effects have led to limitation on the concentrations that can be used in food. Because of that, the analytical determination of these preservatives is important for consumer interest and protection. The purpose of this study is to determine the concentration of sorbic acid in cheese samples by using HPLC. For HPLC analysis, an X-Terra RP-18 (150 × 4.60 mm i.d. × 5 μm) column was selected as the stationary phase at 25°C. Analysis time is about 3 minutes. The developed method was applied to 10 different cheese samples collected from the Turkish market. The levels of sorbic acid in the analyzed samples were between 21.3 mg/kg and 511.3 mg/kg.